Axel Gelfert, A Critical Introduction to Testimony, Londres, Bloomsbury. 2014. 257 pp. - Felipe Álvarez (Mutatis Mutandis: Revista Internacional de Filosofía)
Axel Gelfert, A Critical Introduction to Testimony, Londres, Bloomsbury. 2014. 257 pp.